LANGUAGE ATTITUDES OF BUGINESE SPEAKERS IN BANDUNG - Rusdiansyah Rusdiansyah; Isnendes Retty (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2018)
The aim of this study is to explain the shift in Buginese of the students in Bandung.This is related to the students' language attitude towards Buginese. The use and attitude of language in minority languages in the majority language area is one aspect that influences shifting a language. The method used in this study is a qualitative descriptive method. Research subjects are students from South Sulawesi who are studying in Bandung who are Bugis speakers. The results of this research show that the pattern of language use is dominated by Indonesian when communicating with friends in their area. Although dominated by Indonesian, the use of the Buginese is still used, though not as much as the use of Indonesian. Their language attitude is very positive towards Buginese, but the facts in the field are different from the language attitude, because they are more dominant in using Indonesian than Buginese. This study concluded that the positive attitude of students towards Buginese had no effect on the use of their Buginese. Language preservation depends on the quality of language use in everyday life. The use of Buginese in students in Bandung is relatively low. Students do not maintain their identity as speakers of the Buginese when communicating with each other, thus causing the Buginese to be displaced by Indonesian.